2007
DOI: 10.1111/j.1439-0523.2007.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs related to salinity tolerance of rice at the young seedling stage

Abstract: Using a population of recombinant inbred lines of the 164 genotypes derived from a cross between ÔMilyang 23Õ (indica) and ÔGihobyeoÕ (japonica) in rice (Oryza sativa L.), salt tolerance was evaluated at a young seedling stage in concentrations of 0.5% and 0.7% NaCl. Mapping quantitative trait loci (QTLs) related to salt tolerance was carried out by interval mapping using Qgene 3.0. Two QTLs (qST1 and qST3) conferring salt tolerance at young seedling stage were mapped on chromosome 1 and 3, respectively, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 18 publications
2
60
2
Order By: Relevance
“…Thirtyone F 3 lines derived from the F 2 salt-tolerant plants were used to evaluate the genotypes of F 2 plants. We found that the SM61 mutated salt-tolerance gene, ST8, is located on chromosome 8, different from those previous QTL regions previously discovered on chromosome 1, 3, 4, 5, 6, 7, 9, 10 and 12 (Zhang et al, 1995;Lin et al, 1998;Gong et al, 1999;Prasad et al, 2000;Koyama et al, 2001;Lin et al, 2004;Ren et al, 2005;Lee et al, 2007;Sabouri and Sabouri, 2008). By applying MAS techniques to the gene we have identified as responsible for conferring salttolerance, the results of our study could be used to improve salt tolerance of japonica scented rice.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Thirtyone F 3 lines derived from the F 2 salt-tolerant plants were used to evaluate the genotypes of F 2 plants. We found that the SM61 mutated salt-tolerance gene, ST8, is located on chromosome 8, different from those previous QTL regions previously discovered on chromosome 1, 3, 4, 5, 6, 7, 9, 10 and 12 (Zhang et al, 1995;Lin et al, 1998;Gong et al, 1999;Prasad et al, 2000;Koyama et al, 2001;Lin et al, 2004;Ren et al, 2005;Lee et al, 2007;Sabouri and Sabouri, 2008). By applying MAS techniques to the gene we have identified as responsible for conferring salttolerance, the results of our study could be used to improve salt tolerance of japonica scented rice.…”
Section: Discussioncontrasting
confidence: 51%
“…The materials in our study were different from those in the other reports investigating RIL and DH lines (Zhang et al, 1995;Lin et al, 1998;Gong et al, 1999;Prasad et al, 2000;Koyama et al, 2001;Lin et al, 2004;Ren et al, 2005;Lee et al, 2007;Sabouri and Sabouri, 2008) since the latter derived from crosses between a salttolerant indica and a salt-susceptible parent (Prasad et al, 2000;Lin et al, 2004;Ren et al, 2005) or from two parents without salt-tolerance (Lee et al, 2007). To our knowledge, this is the fi rst study using mapping materials originating from a salt-tolerant japonica line and a salt-susceptible indica variety.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations